Implementation of Discussion Method in Islamic Education Learning to Improve Students' Understanding at SD Negeri 104270 Sukasari - Hayati; Nurman (Journal of Indonesian Primary School, 2024)
This study aims to improve students' learning comprehension in Islamic religious education learning by using the discussion method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to measure learning comprehension and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the understanding of acquisition with the research understanding indicator. The research understanding shows that the discussion method can improve students' learning comprehension in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, the use of the Discussion Method can be used as an alternative to improve students' learning comprehension in Islamic religious education learning.